2021
DOI: 10.3390/land10080879
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Analysis of Price Spillover Effect among Regional Housing Submarkets in Korea: Evidence from the Seoul Metropolitan Area

Abstract: This study examined the price spillover effect of housing submarkets in cities in the Seoul metropolitan area in South Korea by using the Granger causality test and vector autoregressive model (VAR). We found that housing prices showed a higher spillover effect within regions with similar housing market characteristics. Additionally, the spatial spillover of housing prices revealed a difference between sales price and jeonse price. The spillover of jeonse price was characterized by mutual influence among neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…This phenomenon of spatial transmission of housing prices can be called the "spillover effect". This has been confirmed by studies not only in the U.K. [1] but in the U. S. [2], Korea [3], and many other countries as well. Many studies have shown that urban housing prices in China also have an noticeable spillover effect [4][5][6].…”
Section: Introductionsupporting
confidence: 62%
“…This phenomenon of spatial transmission of housing prices can be called the "spillover effect". This has been confirmed by studies not only in the U.K. [1] but in the U. S. [2], Korea [3], and many other countries as well. Many studies have shown that urban housing prices in China also have an noticeable spillover effect [4][5][6].…”
Section: Introductionsupporting
confidence: 62%
“…In 2021, over 400 000 people left Seoul: nearly 90% moved to Gyeonggi, and the remainder to Incheon. This trend has caused a spillover effect in housing costs: as more people are unable to afford the Seoul housing market, housing prices increase in the communities they move to, as do rental costs and rent deposit rates (the "jeonse" system) (Kim and Seo, 2021).…”
Section: Access To Jobs Is More Dependent On Cars Outside Seoulmentioning
confidence: 99%
“…Its development process has important research value. The Seoul Metropolitan Area is the second largest metropolitan area in the world [13].…”
Section: Relationship Between Urban Construction and Railmentioning
confidence: 99%